Human-computer intra-action: a relational approach to digital media and technologies - Hespanhol, Luke (Frontiers in Computer Science, 2023)
The growing pervasiveness of digital technologies has exposed the entanglements of Human-Computer Interaction (HCI) with its surrounding context, from the immediate vicinity of interfaces to global issues. While often providing solutions to societal issues, interactive technologies also many times contribute to them. They impact and are impacted by the world, in a process of continuous mutual influence and co-constitution that raises important implications not only to user experience, effectiveness and efficiency, but also to ethics, social responsibility and environmental health. In this article, I draw on the new materialism notion of intra-action to propose a conceptual shift to a relational approach for HCI, which I refer to as Human-Computer Intra-Action (HCIA), capable of capturing from the outset the inherent relationships with the world that inform the design of interactive technology. To that end, I propose the notion of relationalities to reflect the synergies and antagonisms around those relationships, and discuss emerging notions of spatiality and temporality by considering the increasing hybridity of socio-technical engagements both in space (local versus remote) and in time (immediate versus stretched). Based on that, I propose a preliminary method for mapping intra-actions associated to interactive technologies, envisaged as a starting point to a relational take on their design process.